High frequency of otolaryngology/ENT encounters in Canadian primary care despite low medical undergraduate - Sorichetti, Brendan; Pauwels, Julie; Jacobs, Thomas; Chadha, Neil; Kozak, Emelie; Kozak, Frederick (Canadian Medical Education Journal, 2021)
Otolaryngology involves the treatment of patients with diseases and disorders of the ear, nose, throat (ENT), and related structures of the head and neck. Many medical students in Canada have limited experiences in ENT and a vast majority of these students go on to pursue a career as primary care physicians. Physicians at a primary care facility classified patient’s visits as either being “ENT” related or not, to assess the amount of ENT related concerns they typically encounter. The data was collected separately in the summer and winter months to assess any seasonal variability. One in eight patient encounters presented with an ENT related concern. The percentage of ENT related symptom presentation visits in the pediatric population for both data collection periods (29%) was more than three times that of the adult population (9%). The rate of ENT symptom presentation in both adult and pediatric populations was not affected by seasonality. Primary care physicians will encounter new patients presenting with ENT related concerns quite frequently. This is especially true in the pediatric patient population. Increased ENT medical education is both necessary and essential for undergraduate medical students, residents, and primary care physicians.